$[0, n]\cup \{ω \}$ IS A SPECTRUM OF A NON-DISINTEGRATED FLAT STRONGLY MINIMAL MODEL COMPLETE THEORY IN A LANGUAGE WITH FINITE SIGNATURE. (1st December 2021) - ANDREWS, URI; MERMELSTEIN, OMER
Abstract: We build a new spectrum of recursive models ( $ \operatorname {SRM}(T)$ ) of a strongly minimal theory. This theory is non-disintegrated, flat, model complete, and in a language with a finite signature.